NETWORK ANALYSIS AND OPTIMIZATION USING LOAD BALANCING TECHNIQUES - Mulyana, Dadan; Maulana, Haisyam; Herdiana, Oding; Faridah, Didih (Galuh International Journal of Community Service and Development, 2023)
Internet use is currently growing rapidly in many aspects of life; education, economy, social life, politics and culture. The needs and rapid developments in the use of the Internet network require a balance provision of Internet connection. In fact, connectivity is not always run smoothly because of low bandwidth capacity and network traffic increases. These problems cause network connection interrupted and data lose. Load balancing system is one of the solutions to get a better quality of internet service. Using more than one different ISP (Internet Service Provider) which is then balanced with load balancing system, can make the traffic run optimally, maximize throughput, minimize response time and avoid overload on any of the connection lines. This system worked by distributing the traffic load on two or more connection lines in a balanced way so that traffic can run optimally. By using load balancing system, when the internet is interrupted, then there will be a backup. This study focuses on implementing backups from Internet network sources or backups from dependency on one Internet service provider. The method used in this study is a case study. The instrument used is an observation at the Benteng Village Office in Ciamis. The process started by selecting the right ISP source to be used as a backup. Then continued with the Mikrotik installation and the application of load balancing in Mikrotik. The next steps are testing of the load balancing system which is carried out by technical testing of the implementation. The process includes testing the speed, the function, and optimization of the load balancing. The result shows that the use of load balancing system can be applied optimally. When network traffic increases due to the distribution of balanced connection lanes, it can run without changing the existing network and makes the connection run more optimal.